Campylobacter majalis sp. nov. and Campylobacter suis sp. nov., novel Campylobacter species isolated from porcine gastrointestinal mucosa. Issue 12 (13th December 2022) - Lynch, Caoimhe; Peeters, Charlotte; Walsh, Niamh; McCarthy, Conor; Coffey, Aidan; Lucey, Brigid; Vandamme, Peter
Abstract : Strains LMG 7974 T and LMG 8286 T represent single, novel Campylobacter lineages with Campylobacter pinnipediorum and Campylobacter mucosalis as nearest phylogenomic neighbours, respectively. The results of average nucleotide identity (ANI) and digital DNA–DNA hybridization (dDDH) analyses of LMG 7974 T, LMG 8286 T and type strains of species of the genus Campylobacter confirmed that these strains represent novel species of the genus Campylobacter . The 16S rRNA gene sequences of both strains showed highest identity towards C. mucosalis (97.84 and 98.74 %, respectively). Strains LMG 7974 T and LMG 8286 T shared 72.5 and 73.7% ANI, respectively, with their nearest phylogenomic neighbours and less than 21 % dDDH. The draft genome sizes of LMG 7974 T and LMG 8286 T are 1 945429 bp and 1 708214 bp in length with percentage DNA G+C contents of 33.8 and 37.2 %, respectively. Anomalous biochemical characteristics and low MALDI-TOF mass spectrometry log scores supported their designation as representing novel species of the genus Campylobacte . We therefore propose to classify strain LMG 7974 T (=CCUG 20705 T ) as the type strain of the novel species Campylobacter majalis sp. nov. and strain LMG 8286 T (=CCUG 24193 T, NCTC 11879 T ) as the type strain of the novel species Campylobacter suis sp. nov.